Increased white matter hyperintensities in male methamphetamine abusers - Bae, Soojeong C.; Lyoo, In Kyoon; Sung, Young Hoon; Yoo, Jaeun; Chung, Ain; Yoon, Su-Jung; Kim, Dai-Jin; Hwang, Jaeuk; Kim, Seog Ju; Renshaw, Perry F. (Drug and alcohol dependence, 2006)
The current study was conducted to compare the prevalence, severity, and location of white matter signal hyperintensities (WMH) on brain magnetic resonance (MR) imaging in methamphetamine (MA) abusers. Thirty-three MA abusers and 32 age- and gender-matched healthy comparison subjects were studied. Axial T-2 weighted images and fluid attenuated inversion recovery axial images were obtained using 3.0 T MR scanner. The severity of WMH was assessed separately for deep and periventricular WMH. Ordinal logistic regression models were used to assess the odds ratio for WMH. MA abusers had greater severity of WMH than the healthy comparison subjects (odds ratio: 7.06, 8.46, and 4.56 for all, deep, and periventricular WMH, respectively). Severity of deep WMH correlated with total cumulative dose of MA ( p = 0.027). Male MA abusers had greater severity of WMH than female MA abusers (odds ratio = 10.00). While male MA abusers had greater severity of WMH than male comparison subjects (odds ratio = 18.86), there was no significant difference in WMH severity between female MA abusers and female comparison subjects. The current study reports increased WMH in MA abusers, which may be related to MA-induced cerebral perfusion deficits. In addition, female MA abusers had less severe WMH than male MA abusers, possibly due to estrogen's protective effect against ischemic or neurotoxic effects of MA.